Constructing the vicarious experience of proximity in a Marcellus Shale public hearing. Issue 3 (3rd May 2016) - Mando, Justin
ABSTRACT: This paper examines citizen testimony in a public hearing held within the Marcellus Shale region, USA. By focusing on the role of place as an argumentative resource, this analysis reveals an appeal common to both sides of the issue where hearing participants use their knowledge of a place to provide the audience with the vicarious experience of being in that place. Such scene-making not only provides credibility to average citizens, it is also used to negotiate the communal meaning of place. In this negotiation, fracking supporters are found to be less descriptive and provide an "aerial view" of the places they thematize while fracking opponents represent scenes more closely from an "on-the-ground" perspective with a high level of detail. This difference affects how audience members are invited to engage with these scenes, which may impact the acceptance and circulation of these arguments as well as the way people experience the place they live.